A straightforward method for determining the pulse widths of sinusoidal PWM Waveforms - Escoto, Miguel T. Jr.
A simple, speedy and straightforward method is given for calculating the widths of a sinusoidally modulated pulse train. The method employs the fact that a pulse has its average value proportional to its duty ratio. By setting this duty ratio proportional to the height of a sine wave, the width is thereby easily calculated. The method is shown for the generation of a single phase sinusoidal PWM.